Application of Conjoint Analysis on Student Preferences in Choosing Coffee Shop in Malang City: Study on Undergraduate Students of the Faculty of Mathematics and Natural Sciences, Brawijaya University (Journal of Applied Statistics and Data Science, 2025)
Malang has seen a significant increase in the number of coffee shops. The increasing quantity of coffee shops in Malang is attributed to changes in the local community's lifestyle and the presence of numerous universities with a continually growing student population. The preferences of students in selecting coffee shops in Malang serve as the background for this research. The study aim is to apply traditional conjoint analysis to identify the most preferred attributes and levels by the respondents. The data used is primary data collected through a questionnaires to undergraduate students from the Faculty of Mathematics and Natural Sciences at Brawijaya University, who have visited coffee shops in Malang at least three times. The sampling technique used is nonprobability sampling, namely purposive sampling, with a sample size of 100 respondents. There are six attributes used, that is product, price, atmosphere, service, location, and facilities. The research results indicate the attribute most preferred by the respondents is the price, with a Relative Importance Value (RIV) of 49,66%. The combination of levels for each attribute favored by the respondents includes affordable prices, an indoor atmosphere, comprehensive facilities (Wi-Fi, power outlets, restrooms, prayer room, and spacious parking), a location with smooth traffic flow, a variety of menu options, and service that implements the 5S principles (smile, greet, address, polite, and courteous). Keywords: Attribute, Coffee Shop, Level, Preference, Traditional Conjoint Analysis